Peningkatan Kompetensi Guru dalam Pengembangan Bahan Ajar Digital melalui Pelatihan Pemanfaatan Artificial Intelligence - Guidio Leonarde Ginting; Surya Darma Nasution (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This community service activity was carried out at SMA Negeri 1 Percut Sei Tuan, Kab. Deli Serdang, North Sumatera Province. Based on preliminary observations and interviews, the partner faced the problem of teachers’ low competence in developing digital teaching materials; most teachers still relied on printed textbooks and simple presentation slides, while artificial intelligence (AI) technology had never been utilized to support the preparation of teaching materials. This condition made the learning process less varied and not fully aligned with the characteristics of students as digital natives. This activity aimed to improve teachers’ competence in developing digital teaching materials through training on the use of AI-based applications, including ChatGPT and Gemini for preparing learning materials and assessment instruments, Canva Magic Studio and Gamma for creating interactive slides and digital modules, and Quizizz AI for developing evaluation quizzes. The implementation method consisted of four stages: needs analysis, preparation, training implementation using interactive lectures, demonstrations, and guided practice, and evaluation using pre-test, post-test, product assessment rubrics, and participant response questionnaires. The activity was attended by 25 teachers from various subjects. The results showed an increase in participants’ average comprehension score from 52.4 in the pre-test to 84.8 in the post-test, an increase of 61.8%. All participants (100%) succeeded in producing at least one AI-assisted digital teaching material ready for classroom use, and 92% of participants stated that the activity was very useful and relevant to their professional needs. Thus, the AI utilization training proved effective in improving teachers’ competence in developing digital teaching materials, and its continuation is recommended through periodic mentoring programs so that AI utilization can be integrated sustainably and ethically into learning practices at the partner school.